Pemberdayaan CV Dazry Harapan Melalui Digitalisasi Stok Dan Standar Produksi - Muhammad Hadi Saputra; Sigit Kurniawan; Johandri Iqbal (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: This community service program was carried out to empower the Dazry Harapan Household Industry, a laundry perfume MSME in Jambi City. The partner faced two main problems: business management that was still manual and unstructured production processes. The proposed solutions included the digitalization of transaction and stock recording through a web-based system, the preparation of Standard Operating Procedures (SOP) for production, and digital literacy training. The implementation method consisted of planning, training, mentoring, and evaluation, involving lecturers and students. The results showed that the program targets were achieved: 100% of transactions and stock were recorded digitally, production capacity increased by at least 50%, production cycle time was reduced by 30%, and there were indications of increased revenue and partner satisfaction. This program not only improved business efficiency and product quality consistency but also created a social impact by enhancing the digital literacy of the partner. Furthermore, the program contributes to the achievement of the SDGs (Goal 8: Decent Work and Economic Growth) and university performance indicators. In the future, the developed system is recommended to be integrated with e-commerce platforms to expand market access. Keywords: community empowerment; digitalization; jambi city; sop production; stock management Abstrak: Kegiatan pengabdian kepada masyarakat ini dilaksanakan untuk memberdayakan UMKM parfum laundry Dazry Harapan di Kota Jambi. Mitra menghadapi dua permasalahan utama, yaitu manajemen usaha yang masih manual dan proses produksi yang belum terstruktur. Solusi yang ditawarkan adalah digitalisasi pencatatan transaksi dan stok berbasis web, penyusunan Standar Operasional Prosedur (SOP) produksi, serta pelatihan literasi digital. Metode pelaksanaan meliputi perencanaan, pelatihan, pendampingan, dan evaluasi dengan melibatkan dosen dan mahasiswa. Hasil kegiatan menunjukkan tercapainya target program, yakni 100% pencatatan transaksi dan stok dilakukan secara digital, peningkatan kapasitas produksi minimal 50%, penurunan waktu siklus produksi sebesar 30%, serta adanya indikasi peningkatan omzet dan kepuasan mitra. Kegiatan ini tidak hanya meningkatkan efisiensi usaha dan konsistensi kualitas produk, tetapi juga memberikan dampak sosial berupa peningkatan literasi digital mitra. Selain itu, program ini berkontribusi pada pencapaian SDGs (Tujuan 8: Pekerjaan Layak dan Pertumbuhan Ekonomi) dan IKU perguruan tinggi. Ke depan, sistem digital ini direkomendasikan untuk dikembangkan lebih lanjut melalui integrasi dengan e-commerce guna memperluas akses pasar. Kata kunci: digitalisasi; kota jambi; manajemen stok; pemberdayaan masyarakat; sop produksi